Celebrity Characteristics and Purchase Intentions: A Structural Equation Modeling Analysis of YouTube Culinary Content - Mutiarasari, N Azizia Gia; Hartini, Sri; Sangadji, Suwandi S.; Lina, Lia Febria (Bright Publisher, 2025)
The increasing popularity of YouTube Vloggers has attracted attention in marketing strategies, specifically in the Food Industry. This phenomenon highlights a behavioral shift where relationships between YouTube Vloggers and their followers generate trust, influencing purchase intention. Previous research has explored the formation of parasocial interactions between YouTube vloggers and their followers; this study examined the characteristics of YouTube vloggers that influence credibility and parasocial interactions and the role of these two variables in driving purchase intention, which is still limited. This study collected data through a survey targeting active social media users on Instagram and TikTok who have been exposed to content from YouTube vloggers with food content. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between variables. The results suggest that homophily and social beauty broadly influence credibility and parasocial interactions. In contrast, physical attractiveness only influences credibility, while self-disclosure does not significantly affect parasocial interactions. Credibility and parasocial interactions were found to play an important role in driving consumer purchase intention. This finding strengthens the relevance of the Uses and Gratifications (UG) theory and inducement theory in understanding consumer actions in digitalization.